Trunk control and acute-phase multifactorial predictors of community mobility after stroke: a longitudinal observational study - Alomari, Randah Ahmed; BinMulayh, Ejlal Abdullah; Alqarni, Abdullah Mohammad; Alsobhi, Mashael; Chevidikunnan, Mohamed Faisal; Basuodan, Reem; Khan, Fayaz (Frontiers in Neurology, 2024)
Introduction Stroke is a detrimental condition associated with long-term functional impairments that restrict community reintegration, which is an indicator of successful post-stroke functional recovery and rehabilitation. Additionally, trunk control is an understudied factor that may contribute to community mobility and participation after stroke. This study aimed to identify predictors of community mobility among stroke survivors in the acute phase, with a primary focus on trunk control, in addition to exploring the mediating and moderating role of predictive factors. Methods A longitudinal observational study included 61 participants with acute stroke. Trunk control test (TCT) during sitting, stroke severity, quality of life, fear of falls, depression, and age was assessed during the acute phase as potential predictors. The community mobility outcome measure was assessed 3 months after baseline using the Reintegration to Normal Living Index (RNLI). Statistical analyses included correlation, linear regression, mediation, and moderation analyses. Results Trunk control test was the strongest predictor of RNLI among all factors (β = 0.72; 95%CI = 0.004–0.007; p ≤ 0.0001). Stroke severity, quality of life, fear of falls, and age significantly predicted RNLI (p < 0.01). Higher age was a significant moderator of the relationship between TCT and RNLI (β = 0.002; p < 0.001; 95% CI = 0.0001–0.0003). Discussion The findings highlight sitting trunk control impairment during the acute stage as a crucial predictor of reduced community mobility after stroke, where age over 60 years can moderate this relationship. The study emphasizes that addressing trunk control during early stroke rehabilitation may enhance community reintegration prospects.